Geospace Exploration Project: Arase (ERG) - Miyoshi, Yoshizumi; Shinohara, Iku; Takashima, Takeshi; Asamura, Kazushi; Shiokawa, Kazuo; Higashio, Nana; Mitani, Takefumi; Yokota, Shoichiro; Kasahara, Satoshi; Kazama, Yoich; Wang, Shiang-Yu; Kasahara, Yoshiya; et al. (2017)
18th EISCAT symposium Session E6: The ERG mission and magnetosphere-ionosphere coupling May 26 (Fri), NIPR Auditorium conference object